Frequency of Helicobacter Pylori and Relation of Etiologic Factors who Applied to Firat Medical Center with Dispeptic Complaints - Açik, Yasemin; Gülbayrak, Canan; Dönder, Emir; Yalniz, Mehmet (My University, 2003)
Helicobacter pylori (H.pylori), is generally enfection of microorganism in 70 percentage of world population. Common properties of H.pylori prevalence; enfection is more related with age and more augmentation of enfection prevalence is seen with social and economic bad conditions. Aim of this study is to determine frequency of H.pylori and attract attention to relation of etiologic factors in H.pylori which are designated with patients who had recourse to General Affairs and Gastroenterology policlinics of Firat University with dispeptic complaints. In this study, poll, which formed optional questions, was generally applied and endoscopy was done on 200 patients. H.pylori (+) is positive 81.1% in gastritis, 75.0% in duodenitis, 72.5% in gastroduodenitis and 100% in peptic ülser. Average age of patients of H.pylori (+) is 49.29±14.28 years. H.pylori is determined in 87% percentage of people never gone school and 33.3% of people graduated from university. Certain relation was not found between H.pylori and etiologic factors; incresement risk was determined in low montly pay. As a result, frequency of H.pylori is high level and related with education conditions in patients which were taken investigation in Firat Medicine Center of Firat University. Expensive treatment protocols are insufficient in H.pylori eradication; improvement of social-economic level and general hygienic factors is important in eradication.
Firat Tip Merkezine Dispeptik Yakinmalarla Başvuran Hastalarda Helicobacter Pylori Sikli?i ve Etkileyen Faktörler
Keywords: Dispepsi; Frequency of H.pylori